Contributing Factors in Informal Worker Performance: A Cross-Sectional Study in an Agro-Fish Market in Lamongan, East Java, Indonesia - Tofan Agung Eka Prasetya; Lailiya Mukhadiroh; Cendana Fitrahanjani (Future Science, 2022)
Performance presumably improves and develops the quality of an organization’s products and services. This study analyzed some factors that are likely contributing to informal worker performance as the informal sector has distinct characteristics from the formal one because it is a more flexible setting with no hierarchical position nor fixed income which usually drives worker performance. We analyze worker performance at one of the Agro-Fish Markets in Indonesia, located in Lamongan, East Java. The multifactor leadership questionnaire (MLQ) was used for formulating the leadership styles, while motivation was measured using the multidimensional work motivation scale (MMWS), which was based on Self-determination Theory (SDT). Safety culture was measured using a questionnaire based on the safety culture approach. Performance was assessed using the behavioral anchor rating scale (BARS). The research design is causal explanatory. Our study involved 171 workers. We use the binary logistic regression to identify the relationship between leadership style, motivation, and age towards safety culture as well as the relationship between safety culture and age towards worker performance. We found that safety culture and age could impact 40.1% on worker performance. Although motivation directly impacted safety culture, the study found that it had an indirect impact on performance. The agro-fish market's characteristics as an informal sector may explain why the findings differ from research on the formal sector.